Osteoarthritis of the hip: agreement between joint space width measurements on standing and supine conventional radiographs. Issue 9 (1st September 1998) - Auleley, Guy-Robert; Rousselin, Benoît; Ayral, Xavier; Edouard-Noel, Rachel; Dougados, Maxime; Ravaud, Philippe
Abstract : OBJECTIVE: To assess the effect of standing position on joint space width (JSW) measurements of the hips with and without osteoarthritis (OA) on pelvic radiographs. METHODS: Adult patients aged 18 or more had pelvic anteroposterior conventional radiographs standing and supine performed by a single radiologist in the same radiology unit according to standardised guidelines. JSW measurements in mm were made by a single reader blind to patients' identity and type of view, using a 0.1 mm graduated magnifying glass directly laid over the radiograph, at the narrowest point for OA hips or at the vertical joint space for non-OA hips. Agreement of JSW between both views was assessed using the Bland and Altman graphical analysis. RESULTS: JSW was greater on standing than supine radiographs, for example, 7.1% for OA hips. Mean (SD) differences and limits of agreement (mm) between both views were 0.08 (0.27) and −0.46 to 0.62 for the 70 non-OA hips, 0.02 (0.31) and −0.60 to 0.64 for the 46 OA hips. Corresponding 95% confidence intervals of mean differences were 0.02, −0.14 mm and −0.07, −0.11 mm. CONCLUSIONS: Measurements of JSW of the hip on pelvic standing and supine radiographs are concordant. Changes less than or equal to 0.64 mm between the two views are similar or inferior to radiological progression of OA.